EXTRACTION, IDENTIFICATION AND ANTIOXIDANT POTENTIAL OF SECONDARY METABOLITES OF WHOLE FRUITS OF SANTALUM ALBUM LINNBY GC-MS - Chintamani, Kirti; Dikshit, Madhurima (International Journal of Current Pharmaceutical Research, 2015)
Objective: In order to study the antioxidant potential responsible secondary metabolites the fruit pulp and kernels of Santalum albumwere extracted in different solvents and tried to identify by GC-MS. Methods: The extraction was carried out in various organic solvents by soxhlet by successive manner. The antioxidant capacity of all extracts was determined by FRAP. Identification of various secondary metabolites in the extracts was done by analysing them by GC-MS. Results: Ethyl acetate and methanol extracts of fruit pulp and kernel have shown antioxidant activity. GC-MS identification has shown the presence of many secondary metabolites. Among many compounds cholest-4-en-3-one [11.86 %] obtained as the major constituent in fruit pulp di-chloromethane extract. While kernel methanol extract have showed presence of pyrazinamide [63.70%] and Acetamide-2-cyano [55.40%] in acetonitrile as major compounds. Conclusion: The present study suggests that fruit pulp and kernels of Santalum album can be a new and rich source of medicinally useful secondary metabolites.